2015
DOI: 10.1002/jeab.170
|View full text |Cite
|
Sign up to set email alerts
|

Preference pulses and the win–stay, fix‐and‐sample model of choice

Abstract: Two groups of six rats each were trained to respond to two levers for a food reinforcer. One group was trained on concurrent variable-ratio 20 extinction schedules of reinforcement. The second group was trained on a concurrent variable-interval 27-s extinction schedule. In both groups, lever-schedule assignments changed randomly following reinforcement; a light cued the lever providing the next reinforcer. In the next condition, the light cue was removed and reinforcer assignment strictly alternated between le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…Thus, preference pulses appear to reflect discriminative control by, rather than a transient response‐strengthening effect of, the most recent reinforcer location, or more probably by the location of the response that produced the previous reinforcer. Evidence supporting this has been reported by Hachiga, Sakagami, and Silberberg (; ).…”
Section: Choice Within Interreinforcer Intervalssupporting
confidence: 78%
“…Thus, preference pulses appear to reflect discriminative control by, rather than a transient response‐strengthening effect of, the most recent reinforcer location, or more probably by the location of the response that produced the previous reinforcer. Evidence supporting this has been reported by Hachiga, Sakagami, and Silberberg (; ).…”
Section: Choice Within Interreinforcer Intervalssupporting
confidence: 78%
“…There are already several kinds of simulation theories and they vary in detail, in the phenomena to which they apply, and in generality. A sample of these include those of Catania (2005), Donahoe (2010, 2013), Donahoe & Palmer (1989), Hachiga et al (2015), Li (2019), Li et al (2018a, b), Macdonall (2009), McDowell (2013), McLean et al (2014), Shimp (1969a, 1978, 1979, 1981a, 1984b, 1992, 1994), Shimp et al (1990), Shimp & Friedrich (1993), Tanno (2016), Tanno et al (2015), and Wearden & Clark (1988). Each can generate moment‐to‐moment behavior which can be compared to that of an actual organism (see Li et al, 2018a, b, for related discussion).…”
Section: Usage 10: Combining Shaping and Aggregatingmentioning
confidence: 99%
“…Our analysis showed that the unique effect of primary outcomes, when separated from the general visit structure, was to immediately reduce preference for the just-productive side (but not reverse it to the not just-productive side), which subsequently gradually increased. Our findings are preliminary given the limited literature that has applied McLean et al's (2014) correction to preference pulses (Hachiga, Sakagami, & Silberberg, 2015;Gomes-Ng et al, 2017;Gomes-Ng et al, 2018) and no application to human data to our knowledge.…”
Section: Corrected Preference Pulsescontrasting
confidence: 53%